(3OjhGf GdHGNQRjs - (3GdHGNQRj , Ydj Hf GdMSf Hf Ydj Hf CHj GdWjH, CHh GdMSf,J (B467 (3g` s ((3Ydj Hf CMeO GdeOeGUj s)
(3ChdgG (B:s
(3CeG HYO(B: (3aEf OjhGf GdHGNQRj ETJed Ydi eYGfj aGNJQJ JQJjHgG hLeYgG HGH GdeOjM bGd jeOM GdfHj Udi Gddg Ydjg hSde hBd HjJg s
(3BNQgG (B:s
(3ef bUjOI HGFjI aj HGH GdeQGKj(B: (3gHc WdHJ GdPfhH efj aCjf dj Edg GdPfhH s
(3GfXQ GdLRA GdChd HQbe (B51 (3COH GNJjGQ GdHcQ GdKjH ef SbQ Ydj GHf GdMSf GdWjH hcPdc Qbe (B813 (3COH HYfhGf efJNH OjhGf GdHGNQRjs
(3HChdgG agQSJ ddOjhGf hJQLeI ddeDda ef hajGJ GdCYjGfs
(3hhbajI decJHI CMeO YGQa MceJ HGdeOjfI GdefhQI YGe (B1266 (3g` ef UGMH GdecJHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs